Postmastectomy Breast Reconstruction is Safe in Patients on Chronic Anticoagulation - Yan, Maria; Kuruoglu, Doga; Boughey, Judy C.; Manrique, Oscar J.; Tran, Nho V.; Harless, Christin A.; Martinez-Jorge, Jorys; Nguyen, Minh-Doan T. (Archives of Plastic Surgery, 2022)
Background Postmastectomy breast reconstruction (PMR) increases patient satisfaction, quality of life, and psychosocial well-being. There is scarce data regarding the safety of PMR in chronic anticoagulated patients. Perioperative complications can reduce patient satisfaction; therefore, it is important to elucidate the safety of PMR in these patients.Methods A retrospective case–control study of patients who underwent PMR with implants and were on chronic anticoagulation was performed at our institution. Inclusion criteria were women ≥ 18 years old. Exclusion criteria included autologous reconstructions, lumpectomy, and oncoplastic procedures. Two controls for every one patient on anticoagulation were matched by age, body mass index, radiotherapy, smoking history, type of reconstruction, time of reconstruction, and laterality.Results From 2009 to 2020, 37 breasts (20 patients) underwent PMR with implant-based reconstruction and were on chronic anticoagulation. A total of 74 breasts (40 patients) who had similar demographic characteristics to the cases were defined as the control group. Mean age for the case group was 53.6 years (standard deviation [SD] = 16.1), mean body mass index was 28.6 kg/m2 (SD = 5.1), and 2.7% of breasts had radiotherapy before reconstruction and 5.4% after reconstruction. Nine patients were on long-term warfarin, six on apixaban, three on rivaroxaban, one on low-molecular-weight heparin, and one on dabigatran. The indications for anticoagulation were prior thromboembolic events in 50%. Anticoagulated patients had a higher risk of capsular contracture (10.8% vs. 0%, p = 0.005). There were no differences regarding incidence of hematoma (2.7% vs. 1.4%, p = 0.63), thromboembolism (5% vs. 0%, p = 0.16), reconstructive-related complications, or length of hospitalization (1.6 days [SD = 24.2] vs. 1.4 days [SD = 24.2], p = 0.85).Conclusion Postmastectomy implant-based breast reconstruction can be safely performed in patients on chronic anticoagulation with appropriate perioperative management of anticoagulation. This information can be useful for preoperative counseling on these patients.
Keywords: postmastectomy reconstruction; breast reconstruction; anticoagulation; warfarin; heparin